(untitled) (Research, Society and Development, 2020)
The performance level of structural housing building systems is directly related to quality during the project phases, such as execution and use, and to ensure safety and efficiency in these stages, the buildings must present a minimum level of performance, according to the recommendations of the Brazilian housing performance standard (ABNT NBR 15575). The research involves the qualification of points of non-compliance with the minimum criteria required in NBR 15575/2013 and evaluation of pathological manifestations that affect these buildings. A questionnaire was applied in five works, in the execution phase, with the purpose of diagnosing the knowledge of the builders regarding the minimum recommendations and the application in the new enterprises and, for the evaluation of pathological manifestations, it was raised as observed by the technical team of the works. The results indicate a good level of knowledge about the recommendations, only the topics related to the resistance of reinforced concrete elements, in a fire situation, present indicators below the minimum specifications required. It can be concluded that the procedures adopted by the technical teams, during the design and execution of the housing units, indicate a satisfactory basis regarding the minimum performance of their structural systems.